English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

college algebra

2006-11-24 04:22:09 · 5 answers · asked by koka 1 in Science & Mathematics Mathematics

5 answers

f(x)=-5(x)+7
f0g=-5[-9x^2-4x+5]+7
=45x^2+20x-25+7
=45x^2+20x-18
fog(-9)
=45(-9)^2+20(-9)-18
=3645-180-18
=3447

2006-11-24 04:27:05 · answer #1 · answered by raj 7 · 0 1

f o g means f(g(x))

f(x) = -5x + 7

g(x) = -9x^2 - 4x + 5

Here's how these work: Take your 'f(x)'....if you wanted to know what f(1) was.....that's just: f(1) = -5*(1) + 7

Right?

Then you'd do the arithmetic and come up with: f(1) = 2

Same thing goes with these 'composition' of functions.

f(g(x)) = -5[-9x^2 - 4x + 5] + 7

==> 45x^2 + 20x - 25 + 7
==> 45x^2 + 20x -18

So...f o g = 45x^2 + 20x -18

Do you see?

Now.....you SHOULD be able to do f o g(-9) yourself....it's the SAME kind of thing as I did above with f(1).

2006-11-24 12:29:20 · answer #2 · answered by Anonymous · 0 0

f o g = -5(-9x^2-4x+5) + 7 = 45x^2 + 20x -18

2006-11-24 12:46:59 · answer #3 · answered by ag_iitkgp 7 · 0 0

the answer is 3447 b/c :
g(-9) = -9(-9)^2 - 4(-9) +5
= -688
f(g) = -5(-688)+7
= 3447

2006-11-24 12:37:53 · answer #4 · answered by Gardenia 6 · 0 0

plug in -9 for all the x's in the equation and then multiply the answers together

2006-11-24 12:25:22 · answer #5 · answered by jrtootsiepop 3 · 0 1

fedest.com, questions and answers